Distortive Assumptions in the Literature on White's Thesis: Toward Theologically Sensitive Measures of Dominion and Stewardship Ideology. Issue 1 (March 2023) - Brown, Caleb; Volk, Fred; Wallsgrove, Richard
Since Lynn White's 1967 discussion of Christianity and environmentalism, numerous quantitative sociological studies have attempted to assess whether White's historical claim is born out in Christians' current perspectives. These studies do so in large part by assessing Christians' dominion and stewardship tendencies, about which they make two assumptions: (1) dominion ideology is inherently anti-environmental and (2) dominion and stewardship ideologies are opposed. Many Christians reject these assumptions, a fact we demonstrate by surveying Roman Catholic, Greek Orthodox, and North American Evangelical sources. Each of these discourses, in clear contradistinction to the quantitative sociological literature, portray dominion as leading to self-sacrificial stewardship of creation, all of which is considered intrinsically valuable. Taking a 2015 study of Christians in Nigeria as a case-study, we demonstrate that this conflict between a) the perspectives assumed in the quantitative literature and b) the perspectives held by many Christians leads to a forced and distortive portrayal of these Christians' dominion and stewardship perspectives. Finally, we propose ways of measuring dominion and stewardship perspectives that, while not devoid of assumptions, are flexible enough for Christians to register a variety of competing understandings of these concepts.